Trefftz spectral method for elliptic equations of general type - Reutskiy, Sergiy; Tirozzi, Brunello (Computer Assisted Methods in Engineering and Science, 2001)
A new numerical method for 2D linear elliptic partial differential equations in an arbitrary geometry is presented. The special feature of the method presented is that the trial functions, which are used to approximate a solution, satisfy the PDE only approximately. This reduction of the requirement to the trial functions extends the field of application of the Trefftz method. The method is tested on several one-and two-dimensional problems.